Progress in Laser Accelerator and Future Prospects - Tajima, Toshiki; Chen, Pisin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Laser Wakefield Acceleration (LWFA) has advanced the accelerating gradient many orders of magnitude over the conventional technologies. Their application to high energy accelerators has been considered, while a new field of micrometric accelerators appears for medical applications.